Orientations: Collected Writings - Boulez, Pierre 1925-2016; Nattiez, Jean-Jacques 1945-; Cooper, Martin (Cambridge Harvard University, 1985)
This volume contains a collection of writings by musician Pierre Boulez, who describes his own music and that of other composers, as well as the personalities and institutions with whom he has worked closely.
Keywords: Composing; Music philosophy and esthetics; Music criticism